AN ANALYSIS ON SIAMESE PATRIARCHAL SYSTEMS THROUGH THE FEMALE CHARACTERS’ ACTION AND REACTIONS USING A FEMINISM APPROACH IN ELIZABETH HAND’S ANNA AND THE KING - Anna Sriastuti (Universitas Stikubank (UNISBANK) Semarang, 2011)
Literature pleases humans by imitating life, or more precisely, by displaying its writers’ visions of life as it is or as the writers think it should be. The story of Anna and the King focused more on the struggle of a British teacher in Siam, Anna Leonowens, who was demanded to teach the English ways to Siamese Royal children and wives who still held the traditional culture and rules. The reflections of patriarchal thoughts and views hopefully could be seen through the actions and reactions of Anna and Tuptim. Since the setting of the story influenced the story a lot, it was a need to start the analysis from the analysis of the setting. In conclusion, a broad picture on the Siamese patriarchal systems could be revealed. As a country which held traditions and cultures, Siamese people put the positions of men higher than women. Men had higher position which gave them power to oppressed women for their favors. Polygamy was applied here, which supported the patriarchal power in Siam. Key words: setting, patriarchy, feminism